2018
DOI: 10.12965/jer.1836488.244
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan can improve balance and reduce fear of falling in community dwelling older adults: a randomized control trial

Abstract: Fear of falling and balance impairment are prevalent in older adults and cause major morbidities for this population. The aim of this study was to evaluate the effect of Tai Chi Chuan on balance and fear of falling in community-dwelling older adults. This study was a single-blind randomized control trial. Sixty older adults were randomly allocated into two groups using a 4-cell random block design. The participants of intervention group were trained in Tai Chi Chuan for eight weeks, twice a week, and 55 min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 40 publications
1
61
0
3
Order By: Relevance
“…It is because participants and researchers distinguish their group allocations, and the generalization of findings is limited. Participants are limited to the elderly who live in one condition and they are influenced by their cultural environment, economic situation, and social settings (Hosseini et al, 2018). In research with Visual Feed Back intervention, it shows that recruitment of research subjects based on reported balance problems may result bias sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is because participants and researchers distinguish their group allocations, and the generalization of findings is limited. Participants are limited to the elderly who live in one condition and they are influenced by their cultural environment, economic situation, and social settings (Hosseini et al, 2018). In research with Visual Feed Back intervention, it shows that recruitment of research subjects based on reported balance problems may result bias sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies show that 12 months of practicing Tai Chi Chuan does not change the risk of falling in elderly who live at home. Tai Chi Chuan remains controversial, therefore further studies are needed to explain the benefits of the Tai Chi Chuan program in the elderly (Hosseini et al, 2018). Special training programs for the elderly are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations